2001
DOI: 10.1161/01.str.32.5.1226
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Neuroprotective Effect of Insulin-Like Growth Factor-I After Experimental Transient Focal Cerebral Ischemia Monitored With MRI

Abstract: Background and Purpose-Insulin-like growth factor (IGF) treatment has been shown to have trophic and neuroprotective effects in vitro and in vivo in different lesion models. IGF-I has potent neuroprotective effects after hypoxic-ischemic injury and global ischemia. The role of IGF-I in focal cerebral ischemia is only partially understood. Therefore, in the present study, we evaluated, by applying MRI monitoring, whether a clinically relevant systemic administration of IGF-I can achieve a long-lasting neuroprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(78 citation statements)
references
References 44 publications
5
70
0
1
Order By: Relevance
“…34 Infarct volume was also reduced by IVC injection of 33 g IGF-I per day during 3 days starting 30 minutes after MCAO. 35 Improved functional outcome in this study was observed at Days 1, 2, and 3. When IGF-I was given subcutaneously at a dose of 200 g/day during 7 days starting from 30 minutes after the insult, the infarct volume was reduced and significant improvement of functional outcome was detected at Days 1 and 3 to 7.…”
Section: Studies In Experimental Models Of Ischemic Strokementioning
confidence: 45%
See 2 more Smart Citations
“…34 Infarct volume was also reduced by IVC injection of 33 g IGF-I per day during 3 days starting 30 minutes after MCAO. 35 Improved functional outcome in this study was observed at Days 1, 2, and 3. When IGF-I was given subcutaneously at a dose of 200 g/day during 7 days starting from 30 minutes after the insult, the infarct volume was reduced and significant improvement of functional outcome was detected at Days 1 and 3 to 7.…”
Section: Studies In Experimental Models Of Ischemic Strokementioning
confidence: 45%
“…When IGF-I was given subcutaneously at a dose of 200 g/day during 7 days starting from 30 minutes after the insult, the infarct volume was reduced and significant improvement of functional outcome was detected at Days 1 and 3 to 7. 35 It remains to be established whether IGF-I treatment at later time points reduces or delays functional outcome. Taken together, these results indicate that further studies to the window of opportunity for different ways of administration at different doses are required.…”
Section: Studies In Experimental Models Of Ischemic Strokementioning
confidence: 99%
See 1 more Smart Citation
“…Along with other growth factors (Schabitz et al, 2001(Schabitz et al, , 2003, G-CSF has been previously reported to reduce lesion volume after ischemia in mice (Six et al, 2003) and the rat (Schabitz et al, 2003). In these studies, 50 or 60 mg/kg G-CSF was administered via a single subcutaneous injection, and their findings formed the basis for the present study.…”
Section: Discussionmentioning
confidence: 92%
“…for 3 days, or 200 g/d s.c. for 7 days) beginning 30 minutes after the onset of one hour of ischemia. 32 Infarct volume was reduced by 64% in intracerebroventricularly-treated and by 42% in subcutaneously-treated rats. Another group studied the N-terminal tripeptide of IGF-1, Gly-Pro-Glu (GPE).…”
Section: Igf-1mentioning
confidence: 92%